Refining the understanding of Cretaceous subduction zone processes in the central Indonesian region: The Bantimala Complex (SW Sulawesi) revisited - Bröcker, Michael; Schenk, Volker; Scherer, Erik E.; Soesilo, Joko; Berndt, Jasper (Journal of Asian earth sciences, 2023)
A prominent occurrence of Cretaceous metamorphic rocks in the central Indonesian region is the Bantimala Complex, SW Sulawesi, where an eclogite- and blueschist-bearing sequence is part of an accretionary wedge with a complex internal structure. Zircon U-Pb dating of metamafic blocks indicate a significant protolith age range (c. 369-185 Ma) for the HP/LT rock suite. The HP/LT rocks include lawsonite-free and lawsonite-bearing samples. Lawsonite in eclogite is of retrograde origin. Assuming fast exhumation, multipoint Rb-Sr age data (c. 132-125 Ma) are interpreted to broadly approximate the time of peak HP/LT metamorphism. Existing and new K-Ar and Rb-Sr dates can be subdivided into two groups (c. 137-130 Ma and c. 126-113 Ma). Samples with post-eclogitic lawsonite growth belong to the older age group and all lawsonite-free samples are in the younger age group. The mineralogical and age diversity of various blocks indicates detachment of individual fragments from the subducting plate at different depths, followed by return flow in the subduction channel along different P-T-t trajectories. The role of serpentinite during exhumation remains ambiguous. Field observations offer little support for the suggestion that most HP/LT blocks were originally transported in a serpentinite matrix. Subduction-related magmatism is recorded by a U-Pb zircon age of 109.2 ± 1.1 Ma for a quartz dioritic mélange block. Detrital zircon U-Pb data from a sandstone indicate that tectonic stacking of the Bantimala Complex occurred only after partial erosion of already exposed Cretaceous basement.